Traceability of poultry offal meal in broiler feeding using isotopic analysis (δ13C and δ15N) of different tissues - Oliveira,RP (2010)
Our goal was to trace the inclusion of poultry offal meal (OM) in diets by using carbon (13C/12C) and nitrogen (15N/14N) isotopic ratios of different tissues in order to contribute for the development of an independent technology for the certification of the feeding of broilers reared on diets with no addition of animal ingredients. Eighty one-day-old chicks were randomly distributed into five experimental treatments, that is, diets containing increasing levels of OM inclusion (0, 2, 4, 8 and 16% OM), with four replicates of four birds each. At 42 days of age, four birds per treatment (n=4) were randomly selected, weighed, and sacrificed to collect breast muscle (Pectoralis major), keel and tibia samples to determine their isotopic ratios (13C/12C e 15N/14N). It was observed that 13C and 15N enrichment increased as a function of increasing OM inclusion in all diets. The analyses of the Pectoralis major showed that that only treatments with 8 and 16% OM dietary inclusion were different form those in the control group (0% OM). On the other hand, when the keel and tibia were analyzed, in addition to 8 and 16% OM), the treatment with 4% OM inclusion was also different from the control group. The use of isotopic ratios of stable carbon and nitrogen isotopes is an alternative to trace OM inclusion in broiler diets as it is capable of tracing OM levels below those usually practiced by the poultry industry in Brazil.